GROUND PENETRATING RADAR INVESTIGATIONS FOR ARCHITECTURAL HERITAGE PRESERVATION OF THE HABIB SAKAKINI PALACE, CAIRO, EGYPT - Sayed HEMEDA (International Journal of Conservation Science, 2012)
The modern architectural heritage of Egypt is both varied and vast. It covers all nonecclesiastical buildings, important monumental structures (mansions, municipal buildings) in the history of architecture, as well as more common buildings. They include houses (from mansions to simple dwellings), public buildings (schools, administrative buildings, hospitals), industrial buildings (factories, warehouses, mills), bridges, monastic dependencies (drinking foundations, gardens) and any other modern structures that fall within the category of monuments and comprise the Egyptian cultural heritage. We present herein a comprehensive Ground Penetration Radar (GPR) investigation and hazard assessment for the rehabilitation and strengthening of Habib Sakakini’s Palace, in Cairo, considered one of the most significant architectural heritage sites in Egypt. The palace is located on an ancient water pond at the eastern side of the Egyptian gulf, beside the Sultan Bebris Al-Bondoqdary mosque, a place also called “Prince Qraja al-Turkumany pond”. That pond was drained by Habib Sakakini in 1892, to construct his famous palace in 1897. Eight hundred meters of Ground Penetration Radar (GPR) profiling were conducted, to monitor the subsurface conditions. 600 meters were made in the surrounding area of the Palace and 200 m at the basement. The aim was to monitor the soil conditions beneath and around the Palace and to identify potential geological discontinuities, or the presence of faults and cavities. A suitable single and dual antenna were used (500-100 MHZ) to penetrate to the desired depth of 7 meters (ASTM D6432). The GPR was also used to detect the underground water. At the building basement the GPR was used to identify the foundation thickness and the soil - basement interface, as well as for the inspection of cracks in some supporting columns, piers and masonry walls. All the results, together with the seismic hazard analysis, will be used for a complete analysis of the palace in the framework of the rehabilitation and strengthening works planned for a second stage.